Decision-Making Under Risk and Uncertainty by Substance Abusers and Healthy Controls - Mejía, Diana; Avila-Chauvet, Laurent; Toledo-Fernández, Aldebarán (Frontiers in Psychiatry, 2022)
Cognitive impairment characterized by high impulsivity and risk-taking has been correlated with substance-related disorders. However, it is unclear if the decision-making process is well known upon consideration of factors such as uncertainty environments, risk, and time manipulation in different decision-making procedures. The main objective of this study was to identify behavioral differences between substance abusers and healthy control participants in a behavioral test battery, including (1) two uncertainty decision-making tasks, the Balloon Analog Risk Task (BART) and the Iowa Gambling Task (IGT, trial 1-40); (2) three risk-taking tasks, the Columbia Card Task Hot version (CCT-hot), Columbia Card Task Cold version (CCT-cold), and the IGT (trial 41-100); and (3) an impulsivity task, the Delay Discounting task (DD). The second objective looked at how the six behavioral tests correlate. We worked with a sample of 54 adult participants (Substance abusers: n = 28; Healthy controls: n = 26). An anonymous survey website was created to execute all the cognitive tasks. The results showed no statistically significant differences between the groups in any of the tasks. However, the results showed an upward trend of impulsive (i.e., steeply discounting curve) and risk-taking behaviors (i.e., a low learning curve in IGT) in substance abuse participants. The factor analysis results showed four different main factors: (1) risk-taking task in the IGT (trial 40- 100), (2) uncertainty task in BART, (3) impulsivity in DD, IGT (trial 1-40), and (4) deliberate process in the Columbia card task (cold and hot). We conclude that factors such as the uncertainty tasks in the BART and the first block of IGT trials, the risk cues in the CCT tasks (i.e., number of loss, number of gains, and loss cards), and the time to delivery in the DD task, can affect the complex decision-making process in both clinical and healthy groups. Keywords: Decision making; Discounting; Risk-taking; Substance abuse; Methamphetamine.